Eksistensi Asas Non Self-Incrimination dalam Praktik Plea Bargaining : Studi Komparatif dan Implikasinya dalam Sistem Peradilan Pidana Indonesia - Roli Pebrianto; Noviana Noviana; Muhamad Panji Prabu Dharma (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of modern criminal justice systems demonstrates a growing tendency to prioritize efficiency through expedited case resolution mechanisms, one of which is plea bargaining. This mechanism is increasingly utilized in various legal systems as an alternative approach to reducing case backlogs, accelerating judicial processes, and minimizing litigation costs. On the other hand, criminal procedural law guarantees the defendant’s right to remain silent as an essential component of the principle of non self-incrimination, namely the right not to be compelled to admit guilt or provide evidence against oneself. This study aims to analyze whether the practice of plea bargaining has the potential to undermine this fundamental principle and affect the protection of defendants’ rights within criminal proceedings. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. Legal materials were analyzed to examine the relationship between plea bargaining mechanisms and the protection of procedural rights in criminal justice systems. The findings indicate that plea bargaining inherently contains implicit pressure on defendants to admit guilt in exchange for reduced sentences, lighter charges, or procedural advantages. Such conditions may create an imbalance between procedural efficiency and the protection of fundamental rights, potentially weakening the defendant’s freedom to exercise the right to remain silent. Therefore, careful legal safeguards are necessary to ensure that efficiency-oriented mechanisms do not compromise the principles of fairness, due process, and the protection of human rights in criminal proceedings.